L-Arginine Intake Effect on Adenine Nucleotide Metabolism in Rat Parenchymal and Reproductive Tissues - G. Kocic; J. Nikolic; T. Jevtovic-Stoimenov; D. Sokolovic; H. Kocic; T. Cvetkovic; D. Pavlovic; A. Cencic; D. Stojanovic (The Scientific World Journal)
L-arginine is conditionally essetcial amino acid, required for normal cell growth, protein synthesis, ammonia detoxification, tissue growth and general performance, proposed in the treatment of men sterility and prevention of male impotence. The aim of the present paper was to estimate the activity of the enzymes of adenine nucleotide metabolism: 5′-nucleotidase (5′-NU), adenosine deaminase (ADA), AMP deaminase, and xanthine oxidase (XO), during dietary intake of L-arginine for a period of four weeks of male Wistar rats. Adenosine concentration in tissues is maintained by the relative activities of the adenosine-producing enzyme, 5′-NU and the adenosine-degrading enzyme-ADA adenosine deaminase. Dietary L-arginine intake directed adenine nucleotide metabolism in liver, kidney, and testis tissue toward the activation of adenosine production, by increased 5′-NU activity and decreased ADA activity. Stimulation of adenosine accumulation could be of importance in mediating arginine antiatherosclerotic, vasoactive, immunomodulatory, and antioxidant effects. Assuming that the XO activity reflects the rate of purine catabolism in the cell, while the activity of AMP deaminase is of importance in ATP regeneration, reduced activity of XO, together with the increased AMP-deaminase activity, may suggest that adenine nucleotides are presumably directed to the ATP regenerating process during dietary L-arginine intake.